Multidisciplinary management of a quickly growing pediatric atypical Spitz nevus, mimicking melanoma, during the COVID-19 pandemic - Aurelio Portincasa; Fedele Lembo; Francesca Sanguedolce; Claudio Clemente; Francesco Mazzotta; Domenico Parisi; Liberato Roberto Cecchino (Elsevier, 2023)
Spitzoid melanoma is very rare tumour in the pediatric population, with clinical and non-uniform behaviour, different from adult melanoma [1]. It can be difficult to differentiate an atypical Spitz nevus from a Spitzoid melanoma, resulting in diagnostic problems. In addition, in our clinical case, the COVID-19pandemiccaused significant delays both in the diagnosis and in the surgical treatment of our patient.We present the clinical case of a 4-year-old child suffering from a localized polypoid cutaneous neoformation on the dorsum of the left hand, which started immediately before the lockdown and steadily increased during the COVID-19 pandemic. After a general clinical framing, the child underwent an excisional biopsy at our Department of Plastic and Reconstructive Surgery, at the Policlinico of Foggia. Subsequently, two independent anatomic pathology groups examined the specimen. Definitive diagnosis was made only after careful genetic analysis in combination with supporting histological and immunohistochemical examinations.This clinical case shows how during the pandemic we have been facing advanced forms of tumours, compared to the previous period and highlight show an interdisciplinary and multicenter collaboration allowed a quick diagnosis of certainty, demonstrating the utility of molecular pathology as a fundamental aid in clinical/surgical practice.